Histology of olfactory bulb in the porcupine - Yaman, Mine; Atalar, Omer; Bayrakdar, Ali; Tarakci, Berrin Gencer (Indian Veterinary Journal, 2008)
The rodents, which are the largest order of placental mammals, constitute more than half of the mammals known present day. Porcupine is from the Hystricidae family, which is a small group of the order Rodentia, (Demirsoy 1992). Yaman, et al., (2005) examined somatostatin immunoreactive cells in the porcupine (Hystrix cristata) olfactory bulb. However, no histological details are available on the olfactory bulb of the porcupine. The objective of this study was, therefore to examine the light microscopic appearance of the olfactory bulb in porcupines with an attempt to extend the knowledge in this field.
Keywords: Fibers; System; Rat